Genetic analysis for yield, nutritional and oil quality traits in RIL population of groundnut (Arachis hypogaea L.) - Mukri, Ganapati; Nadaf, H.L.; Gowda, M.V.C.; Bhat, R.S.; Upadhyaya, H. D. (The Indian Journal of Genetics and Plant Breeding, 2016)
A total of 268 recombinant inbred lines (RILs) were evaluated for genetic variability for yield, nutritional and oil quality traits under two consecutive seasons at two locations. Analysis showed that variability exists in the population for the nutritional and oil quality as well as for yield component traits. Majority of the yield components and oil quality traits were governed by additive effects. The nutritional and oil quality traits were not affected by environmental factors and simple phenotypic selection ensures increased performance of the genotypes. Yield components showed moderate to high heritability but with great influence of environment.